PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP KINERJA GURU DENGAN INTERNAL LOCUS OF CONTROL SEBAGAI VARIABEL INTERVENING. (Studi pada guru SMK Negeri 1 Ampelgading Kabupaten Pemalang) - Jamil, Syukron; Liana, Lie (Jurnal Ilmiah Telaah Manajemen, 2018)
This research aims to analyze the influence of intelligence quotients, emotional quotients, spiritual quotients on teacher is performance with internal locus of control as an intervening variable. This research aims to explain and expand previous research, about intelligence, emotional and spiritual quotients on teacher performance with internal locus of control as intervening variable. The research used is explanatory research. The population of this study was as many as 120 teachers at SMK Negeri 1 Ampelgading in Pemalang Regency. Research data is primary data obtained directly from respondents with a questionnaire. The analysis technique in this research uses SPSS version 19. The test carried out includes the analysis of respondents, analysis of variable, validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test and t test. From the results of data testing and data analysis conducted, this research provides results that intelligence quotients has a positive influence on internal locus of control and also teacher performance, emotional quotients has no influence on internal locus of control and teacher is performance, spiritual quotients has a positive influence on internal locus of control and also teacher performance, while internal locus of control has no influence on teacher performance. Another results are internal locus of control does not mediate the influence of intelligence quotients, emotional quotients and spiritual quotients on teacher performance. Keywords: Intelligence Quotients, Emotional Quotients, Spiritual Quotients, Internal Locus of Control, Teacher Performance.